2016
DOI: 10.1111/jfpe.12513
|View full text |Cite
|
Sign up to set email alerts
|

Effects of processing conditions on the system parameters during single screw extrusion of blend containing apple pomace

Abstract: The nutritional profile of apple pomace and soy makes them ideal for development of a new extruded snack food with health benefits. Understanding how blend of apple pomace, defatted soy flour, and corn grits behave under different process conditions during extrusion will help in formulating the extrusion process. Experimental design with apple pomace level (0–20%), barrel and die temperature (100–140 °C), screw speed (100–200 rpm), and moisture content of blend (14–20% wet basis) as independent variables produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 42 publications
1
23
0
1
Order By: Relevance
“…Melt viscosity depends on the extrusion temperature. Earlier we have observed that viscosity decreases with increase in the extrusion temperature (Singha & Muthukumarappan, ). Extrudates obtained at higher temperature had lower bulk density and hence lower hardness.…”
Section: Resultsmentioning
confidence: 73%
“…Melt viscosity depends on the extrusion temperature. Earlier we have observed that viscosity decreases with increase in the extrusion temperature (Singha & Muthukumarappan, ). Extrudates obtained at higher temperature had lower bulk density and hence lower hardness.…”
Section: Resultsmentioning
confidence: 73%
“…Indeed, some extrudates require additional treatment because of conditioning needs, as heating and moisturizing before the extrusion is necessary to achieve proper product quality. For example, for the production of a wide variety of extruded products supplemented with fruits, vegetables or herbs, some thermal treatment is necessitated in order to achieve dry or lyophilized additives, e.g., when tomatoes, apple pomace and vegetable by-products are added to increase nutritional value of extrudates [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Separate attachments have been employed to measure the dough rheology of wheat, corn, and soybeans using straight tube viscometers (Harper, Rhodes, & Wanniger, ), cylindrical dies of different lengths (Harmann & Harper, ), capillary die rheometers (Singh & Muthukumarappan, ,b), and viscoamylographs (Remsen & Clark, ) attached to food extruders. Not only the feed material but the quality of extrudates depends on the type of extruder used, choice of screw configuration, moisture content of the feed, temperature profile in the barrel and die, and screw speed (Singha & Muthukumarappan, ).…”
Section: Introductionmentioning
confidence: 99%